2011
DOI: 10.1038/onc.2011.554
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel CHD1-associated collaborative alterations of genomic structure and functional assessment of CHD1 in prostate cancer

Abstract: A clearer definition of the molecular determinants that drive the development and progression of prostate cancer (PCa) is urgently needed. Efforts to map recurrent somatic deletions in the tumor genome, especially homozygous deletions (HODs), have provided important positional information in the search for cancer-causing genes. Analyzing HODs in the tumors of 244 patients from two independent cohorts and 22 PCa xenografts using high-resolution single-nucleotide polymorphism arrays, herein we report the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 41 publications
11
79
0
1
Order By: Relevance
“…5B and 5C). Taken together, our findings are directly supported by 2 recent studies by Liu and colleagues and Huang and colleagues, who reported tumor suppressor properties of CHD1 while our study was under review (8,9).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…5B and 5C). Taken together, our findings are directly supported by 2 recent studies by Liu and colleagues and Huang and colleagues, who reported tumor suppressor properties of CHD1 while our study was under review (8,9).…”
Section: Resultssupporting
confidence: 80%
“…The ability of clinical prostate cancers to survive and proliferate in the presence of 5q21 deletion may depend on the actual level of CHD1 downregulation, but suggests adaptive mechanisms that provide a selection advantage to CHD1-defective tumors particularly in cancers carrying homozygous deletions. This notion is consistent with the finding that CHD1-depleted prostate cancers harbor additional collaborative genetic alterations (8). An analogous situation has been reported for PTEN, where complete inactivation triggers a p53-dependent fail-safe response inducing growth arrest and senescence both in vitro and in vivo, and which is overcome by defective p53 pathway (29).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…CHD1 was identified as frequently deleted in the homozygous form in prostate cancer [84] and likely contributes to cellular invasiveness [85]. CHD4/Mi-2b has been found to be deleted in a high percentage (17%) of endometrial cancers and is implicated as an autoantigen in the inflammatory disorder dermatomyositis [86].…”
Section: Chd Proteins In Cancer and Other Disease Processesmentioning
confidence: 99%